One-Pot Synthesis of Menthol Starting from Citral over Ni Supported on Attapulgite-H-Beta-38 Extrudates in a Continuous Flow: Effect of Metal Location - Simakova Irina L; Mäki-Arvela Päivi; Martinez-Klimov Mark; Muller Joseph; Vajglova Zuzana; Peurla Markus; Eränen Kari; Murzin Dmitry Yu (AMER CHEMICAL SOC, 2025)
The one-pot synthesis of menthol from citral in a continuous mode was investigated over three different types of extrudates, namely Ni supported on H-Beta-38 and extruded with attapulgite, Ni supported on attapulgite and extruded with H-Beta 38, and the extrudates, which were shaped after deposition of Ni on both H-Beta-38 and attapulgite in the powder form. These composite catalysts were characterized by X-ray diffraction, transmission and scanning electron microscopy, temperature-programmed reduction of H-2, mechanical strength, and pyridine adsorption desorption. These three types of extrudates exhibited different metal particle sizes and acidity. The most promising catalyst in the one-pot menthol synthesis was Ni supported first on H-Beta-38 and then extruded with attapulgite giving a 45% yield of menthols in a trickle bed reactor. This catalyst exhibited 10 nm nickel particles and a rather high amount of strong Bronsted acid sites.